An experimental increase in female mass during the fertile phase leads to higher levels of extra-pair paternity in pied flycatchers Ficedula hypoleuca - Mireia Plaza; Alejandro Cantarero; Juan Moreno (Springer, 2022)
Female mass in most altricial birds reaches its maximum during breeding at egg laying, which coincides temporally with the fertile phase when extra-pair paternity (EPP) is determined. Higher mass at laying may have two different effects on EPP intensity. On the one hand, it would lead to increased wing loading (body mass/wing area), which may impair flight efficiency and thereby reduce female’s capacity to resist unwanted extra-pair male approaches (sexual conflict hypothesis). On the other hand, it would enhance female condition, favouring her capacity to evade mate guarding and to search for extra-pair mates (female choice hypothesis). In both cases, higher female mass at laying may lead to enhanced EPP. To test this prediction, we reduced nest building effort by adding a completely constructed nest in an experimental group of female pied flycatchers (Ficedula hypoleuca). Our treatment caused an increase in mass and thereby wing loading and this was translated into a significantly higher EPP in the manipulated group compared with the control group as expected. There was also a significant negative relationship between EPP and laying date and the extent of the white wing patch, an index of female dominance. More body reserves at laying mean not only a higher potential fecundity but a higher level of EPP as well. This interaction had not previously received due attention but should be considered in future studies of avian breeding strategies.